Hubungan Status Gizi Dan Status Imunisasi Dengan Kejadian Pneumonia Pada Bayi: Hubungan Status Gizi Dan Status Imunisasi Dengan Kejadian Pneumonia Pada Bayi - Vinny Alvionita; Sulfatimah Sulfatimah; Astuti Astuti; Nurfitri Nurfitri (Yayasan Ahmad Mansyur Nasirah, 2022)
Introduction: Pneumonia is an inflammation of lung parenchyma caused by viruses and bacteria such as S. Pnemoniae, M. Pnemoniae, influenza virus, adenovirus, and so forth. To identify the correlation of nutritional status and immunization status with pneumonia in babies in the working area of Pontap Public Health Center of Palopo. This research employed an analytical survey with cross sectional study approach. The population was babies who visited the working area of Pontap Public Health Center. The samples of 62 babies were taken by using accidental sampling technique. Data consisted of primary data (collected through checklist sheet) and secondary data. The data were processed using Statistical Product and Service Solutions (SPSS) and analyzed through univariate and bivariate statistics using Chi-square test and presented in the frequency distribution table. There was a correlation between nutritional status and pneumonia in babies (p Value = ,001 < ,05) and there was an correlation between immunization status and pneumonia in babies (p Value = ,001 < ,05). There is a correlation between nutritional status and pneumonia in babies in the Working Area of Pontap Public Health Center. There is a correlation between immunization status and pneumonia in babies in the Working Area of Pontap Public Health Center. Pendahuluan: Pneumonia adalah peradangan parenkim paru yang disebabkan oleh virus dan bakteri seperti S. Pnemoniae, M. Pnemoniae, virus influenza, adenovirus dan lain sebagainya. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dan status imunisasi dengan kejadian pneumonia pada bayi di wilayah kerja Puskesmas Pontap Palopo. Penelitian ini merupakan penelitian survey analitik dengan pendekatan studi cross sectional. Populasi adalah bayi yang berkunjung ke wilayah kerja Puskesmas Pontap. Sampel sebanyak 62 bayi diambil dengan teknik accidental sampling. Data terdiri dari data primer (dikumpulkan melalui lembar checklist) dan data sekunder. Data diolah dengan menggunakan Statistical Product and Service Solutions (SPSS) dan dianalisis melalui statistik univariat dan bivariat menggunakan uji Chi-square dan disajikan dalam tabel distribusi frekuensi. Ada hubungan antara status gizi dengan pneumonia pada bayi (p Value = ,001 < ,05) dan ada hubungan antara status imunisasi dengan pneumonia pada bayi (p Value = ,001 < ,05). Ada hubungan antara status gizi dengan kejadian pneumonia pada bayi di Wilayah Kerja Puskesmas Pontap. Ada hubungan antara status imunisasi dengan pneumonia pada bayi di Wilayah Kerja Puskesmas Pontap.